Squamous Cell Carcinoma in Non-Functioning Kidney Associated with Staghorn Calculi: Uncommon Presentation of Common Malignancy - Bastakoti, Shankar; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2020)
Cancers of the kidney account for 2% of all the total human cancer. Squamous cell carcinoma (SCC) of renal pelvis is a rare neoplasm, accounting for only 0.5 to 0.8% of malignant renal tumors. In most cases, renal SCC is associated with chronic infections, chronic renal calculi, radiotherapy or any factor that can irritate the urothelium. We report a female patient aged 60 years diagnosed with Right Non-functioning Kidney with Nephrolithiasis with Suspicious Mass. Histopathological diagnosis with Squamous Cell Carcinoma in Stage III with Staghorn Calculi. In long standing urolithiasis, possibility of concomitant harboring of malignancy needs to be taken into consideration.